Factors controlling the emissions of volatile organic acids from leaves of Quercus ilex L.(Holm oak) - Gabriel, R; Schafer, L; Gerlach, C (Atmospheric Environment, 1999)
Direct emissions and emission of precursor compounds of acetic and formic acid from higher plants are a signiÞcant source of these acids in the atmosphere. To travel from the plant cell to the atmosphere, a gas molecule must Þrst leave the liquid phase and then enter the internal leaf gas phase. The apoplast (cell wall) is the last barrier before the molecule can escape through the stomata. During Þeld experiments we monitored the gas exchange (H 2 O, CO 2 , organic acids) of Quercus ilex L. leaves. The exchange rates of acetic and formic acid under Þeld conditions followed a typical diurnal pattern and ranged between!10 (uptake) and 52 (emission) nmol m~2 leaf area min~1 with the maximum around noon. Growth chamber experiments indicate that the emission is related to the stomatal conductance. We discussed the exchange rate of organic acids between the cell wall and the atmosphere in connection with HenryÕs law, and the physicochemical conditions in the cell wall. The evaluation showed that for apoplastic pH values between 4 and 5, 26Ð130% of the measured acetic acid emission based on leaf area could be predicted. ( 1999 Elsevier Science Ltd. All rights reserved.
Keywords: aba abscisic acid; Gas exchange; organic acids; Quercus ilex